An integrated model of social environment and social context for pediatric rehabilitation. Issue 12 (4th June 2016) - Batorowicz, Beata; King, Gillian; Mishra, Lipi; Missiuna, Cheryl
Abstract: This article considers the conceptualization and operationalization of "social environment" and "social context" with implications for research and practice with children and youth with impairments. We first discuss social environment and social context as constructs important for understanding interaction between external environmental qualities and the individual's experience. The article considers existing conceptualizations within psychological and sociological bodies of literature, research using these concepts, current developmental theories and issues in the understanding of environment and participation within rehabilitation science. We then describe a model that integrates a person-focused perspective with an environment-focused perspective and that outlines the mechanisms through which children/youth and social environment interact and transact. Finally, we consider the implications of the proposed model for research and clinical practice. This conceptual model directs researchers and practitioners toward interventions that will address the mechanisms of child–environment interaction and that will build capacity within both children and their social environments, including families, peers groups and communities. Health is created and lived by people within the settings of their everyday life; where they learn, work, play, and love [p.2]. Implications for Rehabilitation: Understanding how social environment and personal factors interact over time to affect the development of children/youth can influence the design of services for children and youth with impairments. The model described integrates the individual-focused and environment-focused perspectives and outlines the mechanisms of the ongoing reciprocal interaction between children/youth and their social environments: provision of opportunities, resources and supports and contextual processes of choice, active engagement and collaboration. Addressing these mechanisms could contribute to creating healthier environments in which all children, including children with impairments, have experiences that lead to positive developmental benefits.